Comparative efficacy of Pseudomonas aeruginosa and anti-Ganoderma fertilizer in managing early-stage Ganoderma boninense infection in oil palm (Elaies guineensis Jacq.) - Halwi, Mohammad Hafizuddin; Abdullah, Siti Nor Akmar; Mohd Amin, Adibah; Rusli, Mohd Hefni; Ahmad, Khairulmazmi (Academic Press, 2026)
Ganoderma boninense causes devastating basal stem rot in oil palm. This study integrates ultrastructural, molecular, and physiological analyses to compare how two control strategies influence early-stage infection mechanisms in infected palms. Roots of oil palm seedlings inoculated with G. boninense and treated with Pseudomonas aeruginosa (T2) or anti- Ganoderma organic fertilizer (T3) were harvested at 5-, 9-, 14-, and 20-days post inoculation (dpi). Untreated G. boninense inoculated seedlings (T1) served as positive control with uninoculated seedlings included as negative controls. Scanning and transmission electron microscopic examination revealed severe cell wall degradation and fungal hyphae proliferation in T1. Both T2 and T3 demonstrated reduced damage albeit T3 offered superior cell wall protection. Pathogen DNA quantification confirmed significantly lower G. boninense DNA levels in T3. RT-qPCR analysis on selected defense response genes revealed that treatment with endophytic bacteria potentially led to earlier activation of ethylene/jasmonate defense signaling pathway while utilization of the anti- Ganoderma fertilizer extended the biotrophic defense response. Enhanced EgGAMYB expression suggests cell wall strengthening in T2 and T3. Ca2+-signaling shift promoted early and more effective defense response in T3. Physiological assessments (chlorophyll index and stomatal conductance) indicated stability in treated seedlings compared to the rapidly degrading T1. Phenotypic observations after 25 weeks showed necrotic roots and leaves in T1, while T2 and T3 resembled healthy controls. Overall, this study extends earlier Pseudomonas -focused studies by directly comparing endophytic bacteria and anti- Ganoderma fertilizer using different evidence, demonstrating their protective effects of and how they differentially modulate biotrophic-to-necrotrophic defense phase transition in oil palm.